Izzivi prenove plačnih sistemov javnega in zasebnega sektorja in kateri od njih so skupni? - Počivavšek, Jakob Krištof (Delavci in delodajalci, 2023)
The article presents reflections on the causes that have led to the need to update wage systems of the public and private sector and on fundamental challenges that arise from those causes and which need to be addressed in collective bargaing and social dialogue. Some of the solutions are also outlined in the article itself.
Keywords: collective agreements; javni sektor; kolektivne pogodbe; minimalna plača; minimum wage; Plače; private sector wage system; public sector wage system; Slovenija; wages; zasebni sektor